AN ANALYSIS ON READABILITY OF ENGLISH READING TEXTS FOR GRADE IX STUDENTS AT MTsN 2 KOTA BENGKULU - Yupika Maryansyah (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2016)
There are many researches on readability of reading materials conducted by reading material experts, but very few investigating readability of reading materials used in teaching reading at state-owned Islamic secondary schools. This research dealt with readability of texts used in teaching reading for IX grade students of a state-owned Islamic secondary school. This research is a descriptive research which used quantitative method. It aimed at investigating the readability of texts used in teaching reading for IX grade students of MTsN 2 Kota Bengkulu. The subjects of this research were 63 texts used in teaching reading for IX grade students at MTsN 2 Kota Bengkulu. The instrument used to collect data was Fry readability formula (graph). The data were interpreted by using percentage.The research findings show that 54% out of 63 texts are easy for grade IX students of MTsN 2 Kota Bengkulu; 27% out of 63 texts are difficult; 10 % out of 63 texts are invalid; and 9% out of 63 texts are appropriate. Based on the research findings, there are some suggestions to note; (1) English teachers at MTsN 2 Kota Bengkulu are suggested to apply readability analysis on texts before they are used in teaching reading; (2) Writers of English textbooks which are intended to be used by grade IX students are suggested to be aware of readability of texts they included into the textbooks they wrote; and (3) other researchers are suggested to conduct further researches on the findings of this research by employing other readability formulas, or other methods of readability analysis.